Thermal performance enhancement of flat plate solar air heater using transverse U-shaped turbulator - A numerical study - M. S. Manjunath; R. Venkatesh; N. Madhwesh (Journal of Mechanical Engineering and Sciences, 2019)
The aim of this study is to determine the effect of U-shaped rib turbulator on the flow and heat transfer characteristics of flat plate solar air heater using two dimensional CFD analysis. The analysis is carried out using the CFD software tool ANSYS Fluent for the flow Reynolds number ranging from 9000 to 21,000.The relative pitch(P/e) of the U-shaped rib is varied as 5, 10, 25 and 40 for a fixed relative rib height of 0.0421. It is shown that the U-shaped rib augments the Nusselt number by about 1.76 times while the friction factor increased by about 1.95 times with reference to smooth duct for a relative pitch of 10 and 5 respectively. The maximum thermal enhancement factor is obtained as 1.5 for the configuration of P/e=25. A comparative analysis of U-shaped rib with circular rib reveals that the U-shaped rib turbulator is found to be more effective in providing heat transfer enhancement and has about 15% higher thermal enhancement factor as compared to circular turbulator.